Portugal as a near shore destination for Information Technology and Business Processes Outsourcing. Factors influencing the location assessment - Lavadera, Michela Lubrano (2016)
This research aims to define Portuguese positioning in the near shoring market for Information Technology and Business Processes Outsourcing. The TAVAAS methodology used throughout this work considers six factors, for which corresponding relative weights were assumed. A qualitative research methodology was conducted to identify the motivational drivers of companies whose transnational services are installed in Portugal. Its results challenged the initial assumption; therefore, they were re-applied to the framework. The deviation from the results achieved with the initial perceived weights was not significant; thus, the initial hypothesis was tested and its results accepted. As conclusion, the relative factor weights to consider when evaluating Portugal as a near shore destination for IT and BPO have been identified.